2017
DOI: 10.1557/jmr.2017.259
|View full text |Cite
|
Sign up to set email alerts
|

A modified constitutive model based on Arrhenius-type equation to predict the flow behavior of Fe–36%Ni Invar alloy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The flow curves obtained during pre-deformation were close to those reported by [34], yet with a slightly lower flow stress, possibly due to a difference in lubrication conditions and strain measurement method. The effects of pre-deformation strain rate and temperature on stress relaxation are shown in Figs 2a and 2b, respectively.…”
Section: Recrystallisation Kinetics Estimated From Stress Relaxation supporting
confidence: 83%
See 3 more Smart Citations
“…The flow curves obtained during pre-deformation were close to those reported by [34], yet with a slightly lower flow stress, possibly due to a difference in lubrication conditions and strain measurement method. The effects of pre-deformation strain rate and temperature on stress relaxation are shown in Figs 2a and 2b, respectively.…”
Section: Recrystallisation Kinetics Estimated From Stress Relaxation supporting
confidence: 83%
“…During the pre-deformation stage, the specimens were first heated up to a given temperature (between 850 and 1050°C) at 30°C/s under a very low compressive stress,  hold , (approximately 4.5 MPa, in order to hold the specimen) and then held for 10 s for temperature homogenisation. They were then compression loaded under displacement control with a constant strain rate up to a 30% axial strain, which is known to be the critical deformation level to trigger dynamic recrystallisation in a similar Fe-32%Ni alloy at 1000°C and 2×10 -3 s -1 [43], and in a Fe-36%Ni alloy [34] in conditions close to those investigated in the present work. After pre-deformation, either the displacement of the anvils was kept constant (see stress relaxation tests in Fig.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…Olga Yakovtseva [ 5 ] used the mathematical Arrhenius constitutive model and artificial neural network model to predict the flow behavior of Al-Zn-Mg alloy, and the results showed that both of them had good predictability, and the prediction accuracy of the artificial neural network model was slightly higher. Shuai He [ 6 ] took the effect of strain on the Arrhenius model′s constants and thermal deformation activation energy (Q) as an independent function, and used the sixth-degree polynomial to perform the fitting. The correlation coefficient (R) and average absolute relative error (AARE) of the measured and predicted data were estimated to be 0.99026% and 3.94%, respectively, which verified the precision of the modified Arrhenius constitutive model.…”
Section: Introductionmentioning
confidence: 99%